The Impact of Stability Factor of Train Operations to Railway Line Capacity (Kroya-Kutoarjo-Yogyakarta) Indonesia - Yuwono Wiarco; Siti Malkhamah; Imam Muthohar; Luzile Mae Satur (Journal of Railway Transportation and Technology, 2022)
Transportation is the backbone of development. It determines the economic growth of a country. Among any modes of transportation, railway is in need to be developed especially in the increasing of railway lines capacity in addition to the development of railway infrastructures, facilities, and the enhancement of rail operational. The determinant in rail operational is the stability in its operation. This stability can be seen by the punctuality of train arrival and departure, which is in accordance with the Graph Train Journey (Gapeka) and “delay” as the indicator. The study was conducted to determine the stability of railway operation and the delay of train travel as well as to identify the effect of the stability of railway operations to the capacity value of railway line. The study was conducted by collecting secondary data and conducting primary survey followed by data analysis. The results showed that the stability of rail operation for Kroya – Kutoarjo - Yogyakarta line was still low with an average delay of 15.60 minutes for double track and 21.68 minutes for single track. There was a decline in capacity when it was compared to the planned capacity or factual practical capacity at 22% on single track and 17% on double track. Further research on how to determine the cause of the instability of railway operation as input for the stability improvement would be needed in addition to the model or formulation to calculate line capacity in corresponding to the conditions in Indonesia.